Characteristics of low-angle normal faulting in Serifos (Western Cyclades, Greece) - Grasemann, B.; Schneider, D. A.; Iglseder, C.; Tschegg, C. (TRABAJOS DE GEOLOGÍA, 2009)
On the island of Serifos SSW-directed low-angle faults accommodated crustal thinning during Miocene extension. Cross-cutting relationships suggest that the low-angle faults interacted with WNW-ESE striking conjugate high-angle normal faults in both the hanging and the footwall. Although high- and low-angle faults were likely synkinematic, the deformation mechanism differs significantly in both systems. The low-angle faults are characterized by several meters of low-grade, ultrafine grained marble mylonites below several decimetres of ultracataclasites. The high-angle faults represent mainly brittle deformation resulting in slickensides, cataclasites and pseudotachylites. The Ar/Ar mica geochronology yields uniform ages across the low-angle faults suggesting a nearly horizontal detachment at temperatures coincident with the brittle-ductile transition zone.